Estudo da caracterização química e atividade biológica das folhas e do óleo essencial de Ottonia corcovadensis - Fontoura, Bruno Henrique (2023)
Ottonia corcovadensis is a plant native to Brazil, widely used in folk medicine, popularly known as “João brandinho”. The objective of this work was to optimize the extraction conditions and develop a predictive chemometric model using digital images to determine the antioxidant, antimicrobial, cellular cytotoxicity, oxidative stress of the ethanolic extract and also of the essential oil, as well as its chemical composition. a combination of the factors solvent concentration, temperature and extraction time were performed and the results treated by the generalized linear model (MLG), evaluated for the content of total phenolic compounds, antioxidant activity (ABTS, DPPH and FRAP), antimicrobial activity (MIC and MBC), cell viability (MTT), biochemical markers of oxidative stress. The chemometric model was developed using the random forest (RF) algorithm, using the analysis of total phenolic compounds (CFT) and DPPH antioxidant activity. The best extraction condition was the 80/20% ethanol/water ratio, at 80 ºc in a water bath for 120 min, which obtained a result of 11.64 mg EAG g-1 and 21.27 mg Trolox g-1 for CFT and DPPH. the extract did not show cellular cytotoxicity and antitumor activity, nor change in oxidative stress markers and did not show antimicrobial activity. For the essential oil, it was possible to identify 38 compounds, the majority of which were E-sesquisabinene hydrate, E-caryophyllene, ß-pinene, E-ß-farnesene, which showed antioxidant activity by abts and dpph with values of 2.88 and 6 .26 mg trolox g-1 respectively, and cft of 5.41 mg EAG g-1, also did not show cell cytotoxicity and showed antitumor activity at concentrations of 62.50 and 250 μg mL-1, no alterations in the markers of oxidative stress and showed antimicrobial activity against the microorganisms Bacillus subtilis, Listeria monocytogenes and Salmonella typhimurium, Escherichia coli at the concentrations 10.46 and 2.61 ug mL-1 tested. In this way, the ethanolic extract and essential oil can be considered with antioxidant, non-cytotoxic antimicrobial potential and the essential oil has antitumor potential.